Efficient cell capture in an agarose–PDMS hybrid chip for shaped 2D culture under temozolomide stimulation. Issue 79 (9th August 2016) - Lin, Luyao; Jie, Mingsha; Chen, Fengming; Zhang, Jie; He, Ziyi; Lin, Jin-Ming
Abstract : Arbitrary cell patterning on an agarose microwell array is realized and applied to study glioma cell cultures under temozolomide stimulation. Abstract : In this work, hybrid microfluidic devices were fabricated by assembling a polydimethylsiloxane (PDMS) mold with an agarose microarray to realize cell capture and patterning in precisely controlled spatial distribution. Microwells with diameter varying from 15 to 30 μm were formed on the agarose hydrogel surface at 15 μm to 40 μm spacing. Cells were efficiently captured in microwells with nearly 100% occupancy, thus achieving cell manipulation in a semi-quantitative manner. The size of the cell population captured on the microwell array is proportional to the patterning area. Further study revealed that the capture process was mainly regulated by fluid dynamics, where liquid was absorbed by the highly permeable agarose substrate and carried target cells into microwells. Our method spared the complex chemical modification steps, and the agarose substrate promised good biocompatibility. By designing PDMS channels with different geometrical layouts, various cell patterning geometries were easily created. Cell culture models with controllable pattern area and population size were successfully developed for a temozolomide stimulation study for as long as 2 days. This work should benefit the study of cancer developing niche and provide a powerful platform for the direct and continuous observation of cell dynamics under drug stimulation.